PacBio single-molecule long-read transcriptome sequencing and analysis of somatic embryogenesis in Picea mongolica - Dai, Jinling; Zhang, Shengli; Bai, Yu’e (Frontiers in Plant Science, 2025)
IntroductionPicea mongolica is an endangered conifer species endemic to Hunshandak Sandy Land, uniquely adapted to extreme desert conditions. However, it faces critical conservation challenges due to slow regeneration rates, limited seed production, and high susceptibility to pathogens, which collectively threaten its population sustainability and genetic diversity. MethodsWe performed long-read transcriptome sequencing of pooled samples from various somatic embryogenesis stages using PacBio SMRT technology. The obtained transcripts were functionally annotated using the Nr, SwissProt, KEGG, and KOG databases. We conducted comprehensive transcript structure analyses, including identification of alternative splicing, SSR loci, lncRNAs, and transcription factors. Furthermore, we cloned the PmBBM gene and analyzed its sequence characteristics. Expression patterns of PmBBM and other AP2 transcription factor family members during somatic embryogenesis were profiled. ResultsOur analysis generated 12,232 high-quality transcripts. We identified 83 genes with alternative splicing, 1,006 SSR loci, 35 lncRNAs, and 548 transcription factors from 46 distinct families. The PmBBM gene was successfully cloned and characterized. Expression profiling revealed dynamic expression patterns of PmBBM and other AP2 family members across different stages of somatic embryogenesis. DiscussionThis study establishes the first reference-quality transcriptome database for P. mongolica using PacBio long-read sequencing, providing essential genomic resources for this non-model species. Our findings not only enhance the understanding of molecular mechanisms in somatic embryogenesis but also lay a foundation for future functional genomics research, including gene validation and molecular marker-assisted breeding. These results have significant theoretical and practical implications for the conservation and sustainable utilization of this endangered conifer.